HIGH RESOLUTION BIOSTRATIGRAPHY AND PALEOECOLOGY OF THE EARLY PLIOCENE SUCCESSION OF PISSOURI BASIN (CYPRUS ISLAND) - Triantaphyllou, M. V; Antonarakou, A.; Drinia, H.; Dimiza, M. D.; Kontakiotis, G.; Tsolakis, E.; Theodorou, G. (Bulletin of the Geological Society of Greece, 2010)
The Pissouri basin (Cyprus Island) corresponds to a small tectonically controlled depression elongated NNW-SSE and widening southward in the direction of the deep Mediterranean domain. In the centre of the basin, the section Pissouri South, about 100 m thick, consists of well-preserved cyclic marine sediments including laminated brownish layers alternating with grey homogeneous marls. Plankton biostratigraphy (calcareous nannofossil and planktonic foraminifera) revealed a remarkable number of biovents bracketing the Zanclean-Piacenzian boundary. In particular the Highest Occurrence (HO) of Reticulofenestra pseudoumbilicus suggests the presence of NN14/15-NN16 nannofossil biozone boundary, dated at 3.84 Ma. Additionally the defined planktonic foraminiferal MPL3-MPL4a and MPL4a-MPL4b zone boundaries point to ages between 3.81 and 3.57 Ma, in Pissouri North section. Zanclean/Piacenzian boundary (3.6 Ma) is placed at 75.8 m from the base of the section, considering Discoaster pentaradiatus top paracme (3.61 Ma) and Globorotalia crassaformis first influx (3.6 Ma) bioevents. The cyclically developed sapropelic layers around the Zanclean – Piacenzian boundary suggest a climate characterized by a period of warm temperate conditions and a highly stratified water column that occurred at times of precession minima.